A capsule-deficient mutant of Francisella tularensis LVS exhibits enhanced sensitivity to killing by serum but diminished sensitivity to killing by polymorphonuclear leukocytes. - Sandström, G (1988)
The live vaccine strain (LVS) of Francisella tularensis is killed by human polymorphonuclear leukocytes as a result of strictly oxygen-dependent mechanisms (S. Löfgren, A. Tärnvik, M. Thore, and J. Carlsson, Infect. Immun. 43:730-734, 1984). We now report that a capsule-deficient (Cap-) mutant of LVS survives in the leukocytes. In contrast to the encapsulated parent strain, the Cap- mutant was avirulent in mice and was susceptible to the bactericidal effect of nonimmune human serum. The mutant was killed by serum as a result of activation of the classical pathway of complement by naturally occurring immunoglobulin M. This killing by serum was mitigated by the presence of human polymorphonuclear leukocytes. After opsonization in complement component C5-deficient nonimmune serum, the Cap- mutant was ingested and survived in the leukocytes. Under these conditions, the parent strain was killed. The leukocytes responded to both the parent and the Cap- strain with a very low chemiluminescent response. Only the response to the parent strain was inhibited by superoxide dismutase. When the Cap- mutant was opsonized with immunoglobulin G, it induced a higher and superoxide dismutase-inhibitable chemiluminescent response and was killed by the leukocytes. In conclusion, the capsule of F. tularensis LVS seemed to protect this organism against the bactericidal effect of serum. When deprived of the capsule, the organism failed to induce an antimicrobial response in polymorphonuclear leukocytes and survived in the leukocytes. Survival in phagocytes is a key characteristic of intracellular parasites. The Cap- mutant of F. tularensis may become a useful tool in experiments to explain the differences between pathways of ingestion of intracellular parasites, evidenced by the death or survival of the parasite.